Mucosal papillary hyperplasia in gallbladder: A clue for infectious etiology in HIV patients - Juhi Devendra Mahadik; Ramya Prakash Masand; Shilpa Jain (Journal of Global Infectious Diseases, 2021)
Gallbladder specimens are ditzel in surgical pathology and opportunistic diseases like cryptosporidiosis where they are easy to miss. We describe three cases of gallbladders with mucosal papillary hyperplasia with acute and chronic inflammation, all of which revealed cryptosporidiosis on complete histological evaluation. The patients were found to be HIV positive on further chart review. In the absence of clinical history, which is often the case with gallbladder specimens, the finding of mucosal papillary hyperplasia can be a reactive response to an infectious cause and can serve as a helpful clue to look for organisms with patience at higher magnification.